The Influence of Collective Asynchronous Discourse Elaborated Online by Pre-Service Teachers on Their Educational Interventions in the Classroom - Allaire, Stéphane (Canadian Journal of Education/Revue canadienne de l’éducation, 2015)
Networked learning communities are growing and they offer new opportunities for reflection on practice in education. Many authors have studied the processes followed and the contents produced by such communities. On the other hand, few have observed how collective asynchronous discourse can be enacted in the classroom. This objective was pursued in the context of this exploratory research. Data was provided by asynchronous discourse written on the Knowledge Forum by five pre-service teachers during a 14-week practicum throughout the winter 2011 semester, as well as in situ observations from their university supervisor, while they were teaching students. Qualitative and descriptive quantitative analyses were conducted. In particular, results showed participants were highly concerned with quality of teaching when elaborating collectively in the electronic forum regarding ideas of interventions, and with the importance of properly handling the possible enactment of such ideas in the classroom while teaching.